All types of coherent radiations, which arise in the collision of relativistic electrons with crystal - Morokhovskii, V.L. (Вопросы атомной науки и техники, 2015)
The general quantum theory, that describes all types of X-and-γ-rays coherent radiations, which arise in the collision of relativistic electrons with a crystal target, is described briefly. Such types of coherent radiations as: ordinary coherent bremsstrahlung and channeling radiation, emitted by a relativistic electron; different types of coherent polarization radiations, emitted by the crystal atoms and nucleus; the interference of these two types of coherent radiations can be described within the framework of the present theoretical model.